THE RELATIONSHIP BETWEEN SOFT FACTORS AND HARD FACTORS OF TQM PRACTICES AND ORGANIZATIONAL LEARNING - Sisnuhadi (European Scientific Journal, ESJ, 2014)
This study examinesthe relationships amongsoft factors and hard factors of total quality management (TQM) practices, and organizational learning in Indonesia’s ISO 9001registered manufacturing companies. As many as 217 quality managers in Indonesia’s ISO 9001 registered manufacturing companies participated in this study. The results of this study found that in Indonesia’s ISO 9001 registered manufacturing companies, the higher levels of soft factors lead to higher levels of hard factors and organizational learning. Hard factorsinsignificantly affect organizational learning;therefore hard factors do not mediate the relationship between soft factors and organizational learning.